Evaluation on applicability of a new hybrid adsorbent to waste pollution control in Lowland by complex leachate from waste landfill site - S. Juengjarernnirathorn; M. Ohno; Y. Mishima; H. Suhara; H. Araki (International Association of Lowland Technology, 2016)
There is growing social concern about water environment issue including eutrophication, water pollution in the water bodies, and hazardous contaminants in lowland groundwater. Following extensive research into wastewater characteristics, the understanding of the potential effects of wastewater on health and the environment has become more comprehensive. Soil and water in lowland areas are especially easily contaminated by heavy metals, toxicant chemicals from waste disposal landfill sites and factories, and natural disasters. These events have prompted the search for suitable solutions. Several treatment methods have been developed to deal with health and environmental concerns associated with the findings of recent research. In this paper, a new adsorbent is characterized and the adsorption of harmful substances dissolved in leachate has been studied. Nano size Layered Double Hydrotalcite (NLDH) and Zeolite (Ze) have been combined to synthesize a more powerful adsorbent, which successfully adsorb both anion and cation at the same time; cations and anions were simultaneously recovered at the same time over 3 hours, under an initial pH of 6 at 20°C using 0.5 gram and 1 gram per liter of the hybrid adsorbent (HB). Other adsorbents were used to validate the efficiency of a new hybrid adsorbent (HB).